(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This paper deals with the results of a revision on the genus Lecanopsis Targioni Tozzetti (Coccidae) carried out during the last years. The revision highlighted synonymies among species and misidentifications of species erroneously placed in this genus. Before the present revision the genus included 17 species, but at the end of this study the number of Lecanopsis species was reduced to 11, plus 3 unrecognisable species. All the Lecanopsis species and their young instars (when known) have been redescribed and illustrated. In addition, two new species, L. marottai and L. mirabilis, recently collected in Italy, are described and illustrated.